(untitled) (Ofioliti, 2007)
- HIGH - TEMPERATURE SHEAR FLOW IN THE CRUST AND UPPER MANTLE: IN SEARCH FOR RELATIONSHIPS AND GEODYNAMIC SETTING R.L.M Vissers - MICROSTRUCTURES IN HOLE 1274, ODP LEG 209, MID-ATLANTIC RIDGE - TRACKING THE FATE OF MELTS PERCOLATING IN PERIDOTITE AS THE LITHOSPHERE IS INTERCEPTED G Suhr, Leg 209 Scientific Party - THE COMPOSITE STRUCTURAL FRAMEWORK IN VARISCAN HIGH-GRADE METAMORPHICS: AN EXAMPLE FROM THE PORTO OTTIOLU-PUNTA DE LI TULCHI AREA (NE SARDINIA, ITALY) B. Corsi, G. Cruciali, F.M. Elter, M. Franceschelli, P. Balbi, G.L. Mallus - GEOMETRY OF DEFORMATION, STRAIN FEATURES AND DISTRIBUTION OF MAGMATIC-BODIES IN THE HIGHER HIMALAYA CRISTALLINE BETWEEN KARTA AND TINGRI (TIBET-HIMALAYA) G. Molli, G. Musumeci, D. Iacopini and P.C. Pertusati - PLUTON EMPLACEMENT IN THE LAB - WHAT WE CAN LEARN FROM ANALOGUE CENTRIFUGE EXPERIMENTS ABOUT THE BEHAVIOUR OF GRANITOID BODIES C. Dietl and H. Koyi - RHEOLOGY AND DEFORMATION OF PARTIALLY MELTED CRUSTAL ROCKS C.L. Rosenberg - EMPLACEMENT MECHANISMS OF THE LATE-OROGENIC GRANITES IN SW FINLAND - A HISTORY OF REPEATED INTRUSIONS AND STRUCTURAL CONTROL C. Ehlers T. Stålfors and T. Torvela - THE ROLE OF HIGH-T SHEAR ZONES IN EXHUMATION OF AN OROGEN: INSIGHTS FROM THE VARISCAN GRANULITIC-AMPHIBOLITIC METAMORPHIC BASEMENT IN SOUTHEAST CORSICA (FRANCE) F. Giacomini, L. Dallai, E. Carminati, M. Tiepolo and C. Ghezzo - GABBROIC BODIES IN THE TRINITY OPHIOLITE K. Stremmel and G. Suhr - MYLONITIC GNEISS IN THE VARISCAN BASEMENT AT PUNTA ORVILI, NE SARDINIA, ITALY G. Cruciani, F.M. Elter, M. Franceschelli, D. Uteri, B. Corsi and G.L. Mallus - RECORD OF LITHOSPHERIC THINNING IN THE SUBCONTINENTAL MANTLE (EXTERNAL LIGURIDE OPHIOLITES, NORTHERN APENNINE, ITALY): FROM RIFTING TO CONTINENTAL BREAKUP A. Montanini and R. Tribuzio - QUARTZ C-AXIS PATTERNS DURING THE GRANITOIDS COOLING: EXAMPLES FROM THE LATE HERCYNIAN MID-CRUSTAL SHEAR ZONE OF SILA MASSIF (CALABRIA, SOUTHERN ITALY) V. Festa and D. Lotta - DIFFERENT MELT FRACTIONS IN A SINGLE MIGMATITE BELT: THE ROLE OF ROCK-COMPOSITIONS, FLUID-INFILTRATION PATHWAYS AND TECTONICS A. Berger - ULTRAMAFIC PSEUDO-TACHYLITES IN THE MONCUNI OPHIOLITIC PERIDOTITE (LANZO MASSIF, WESTERN ALPS): RECORDS OF EARTHQUAKES DURING FORMATION OF THE JURASSIC LIGURIAN TETHYS M. Marasco, G.B. Piccardo and A. Pruzzo - TECTONIC AND MAGMATIC PROCESSES IN A FOSSIL ULTRA-SLOW SPREADING OCEAN: THE STUDY CASE OF THE JURASSIC LIGURIAN TETHYS G.B. Piccardo - EXTENSIONAL DEFORMATION, MANTLE MELTING AND MELT PERCOLATION IN THE ERRO-TOBBIO PERIDOTITE (VOLTRI MASSIF, LIGURIAN ALPS) R.L.M. Vissers and G.B. Piccardo - SHEAR ZONES IN THE MANTLE: THE ROLE OF METAMORPHIC AND MELT-ROCK REACTIONS (Invited Contribution) A.H. Dijkstra - THE OTTANA-MT.E’ SENES SHEAR ZONE (CENTRAL SARDINIA, ITALY): CONSTRAINTS ON A MAJOR OROGEN-NORMAL SHEAR ZONE OF LATE VARISCAN AGE C. Ghezzo, F. Giacomini, E. Sartia and F.M Elter - MELT MIGRATION AND HIGH TEMPERATURE SHEAR ZONE IN THE UPPER MANTLE (LANZO MASSIF, ITALY) M.A. Kaczmarek, and O. Müntener - EMPLACEMENT OF MAGMATIC BODIES AND ACTIVATION OF SHEAR ZONES IN THE COUNTRY ROCKS: AN EXAMPLE FROM EASTERN ELBA ISLAND (TUSCAN ARCHIPELAGO, ITALY) Serena Vannetti, Enrico Pandeli, and Franco Marco Elter